2013
DOI: 10.1111/risa.12149
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Change in Risk Perception and Optimistic Bias for Hurricanes Among Gulf Coast Residents

Abstract: This study focuses on levels of concern for hurricanes among individuals living along the Gulf Coast during the quiescent two-year period following the exceptionally destructive 2005 hurricane season. A small study of risk perception and optimistic bias was conducted immediately following Hurricanes Katrina and Rita. Two years later, a follow-up was done in which respondents were recontacted. This provided an opportunity to examine changes, and potential causal ordering, in risk perception and optimistic bias.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 72 publications
(114 reference statements)
5
68
0
2
Order By: Relevance
“…For example, people who had recently suffered damage in a wildfire gave higher estimates of the likelihood of a future fire, compared to those who had not suffered damage [42]. In the case of hurricanes, Trumbo et al [43] found that during the quiescent three-year period after the 2005 hurricane season, when Katrina and Rita struck, hurricane risk perception declined and optimism bias (believing others are more likely to suffer harm than oneself) increased. Additional evidence of a recency effect on preparation decisions can be found in voluntary flood insurance purchases, which were predicted in one study by peak storm surge heights during the most recent hurricane [44].…”
Section: Prior Storm Experiencementioning
confidence: 99%
“…For example, people who had recently suffered damage in a wildfire gave higher estimates of the likelihood of a future fire, compared to those who had not suffered damage [42]. In the case of hurricanes, Trumbo et al [43] found that during the quiescent three-year period after the 2005 hurricane season, when Katrina and Rita struck, hurricane risk perception declined and optimism bias (believing others are more likely to suffer harm than oneself) increased. Additional evidence of a recency effect on preparation decisions can be found in voluntary flood insurance purchases, which were predicted in one study by peak storm surge heights during the most recent hurricane [44].…”
Section: Prior Storm Experiencementioning
confidence: 99%
“…Some studies have shown that females are significantly more likely than males to reloacte/evacuate (Whitehead et al 2000;Bateman and Edwards 2002;Lazo et al 2015;Lim et al 2016), although Stein et al's (2013) study showed that gender had no significant impact on household evacuation willingness. Some studies have shown that older residents are more likely to relocate/evacuate than other age groups (Lazo et al 2015), but others have found the opposite effect (Kaniasty and Norris 1995;Trumbo et al 2014;Lazo et al 2015) or no effect (Huang et al 2012;Stein et al 2013). A few studies have shown that individuals with higher educational levels were more likely to relocate/evacuate than others (Hasan et al 2011), as well as revealing other differences in evacuation decision making (Whitehead et al 2000;Stein et al 2013;Lazo et al 2015;Lim et al 2016).…”
Section: Individual Characteristics and Relocation/ Evacuation Willinmentioning
confidence: 99%
“…Some studies have found that relocation/evacuation likelihood increased with income (Bateman and Edwards 2002;Dash and Gladwin 2007), decreased with income (Trumbo et al 2014), or was insensitive to income (Whitehead et al 2000;Huang et al 2012;Stein et al 2013;Yang 2016). Lazo et al (2015) found that household size had no significant impact on household evacuation willingness.…”
Section: Household Characteristics and Relocation/ Evacuation Willingmentioning
confidence: 99%
“…However, because our survey was conducted approximately two years after Hurricane Sandy made landfall, it is possible that survey responses may reflect, in part, inaccuracies in recall that are likely to intrude as the time between a remembered event and the present grows larger . For instance, hurricane risk judgment may change over time, such that individuals develop an increasing optimistic bias—i.e., the propensity to see others as more at risk than oneself; lacking longitudinal measurement of study variables, we cannot determine whether this might have been the case among this study sample. Second, as mentioned above, the cross‐sectional nature of the data limit inferences about causal relationships between key study variables.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, risk judgment may change over time, especially as the distance between the present and one's experience with the weather or natural‐hazard‐related risk increases . For instance, in a longitudinal study of Gulf Coast residents, hurricane‐related risk perception decreased over time while optimistic bias—i.e., perceiving the risk posed to others as greater than risk to self—increased; however, in a longitudinal study of homeowners in Colorado, Champ and Brenkert‐Smith show that perceptions of wildfire risk remained relatively stable, despite intervening wildfire in the area. While recall accuracy for past events is likely to diminish over time, opening the way for a host of biased judgments in general, self‐reported assessments of risk are likely to vary across individuals and contexts given the reconstructive nature of memory and the largely heuristic (vs. systematic) nature of the inferential processes that guide cognitive retrieval and reporting.…”
Section: Literature Reviewmentioning
confidence: 99%